Simulating the effects of refractive index difference on the coupling efficiency of periodically segmented waveguide mode converter - Zheng, Yu; Jiang, Lianqiong; He, Hao; Duan, Ji’an (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
Efficient coupling of micro/nano-optical waveguides with single-mode fibers is the premise for the efficient operation of the integrated photonic chip, which directly determines its optical performance. In this paper, the design principles of periodically segmented waveguide (PSW) structure used for high-efficiency fiber-chip coupling are proposed, and the effects of refractive index difference Δ on coupling efficiency and structural parameters are studied by simulation. It is found that as the Δ of the PSW increases, the period of the PSW tends to be smaller, and the coupling efficiency decreases continuously, reduced by around 0.673 dB in the range of Δ = 3% to Δ = 7%. Through the analysis of PSW optical mechanisms, it demonstrates that the main reason for the decrease of coupling efficiency is that the transmission loss of the tapered section increases sharply with the increase of Δ. High-Δ PSW is difficult to apply to highly integrated silica optical chips due to the unignorably insertion loss.
Optica Applicata, Vol. 51, 2021, nr 4, s. 565-577
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; coupling efficiency; silica waveguide; planar lightwave circuit; micro/nano-optical waveguide